1996
DOI: 10.1159/000267960
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Distribution in the Human Eye Lens

Abstract: The distribution of calcium in the human eye lens was investigated using the oxalate-pyroantimonate technique. In epithelial cells and superficial cortical fibers calcium is sequestered and tightly bound to proteins in the endoplasmic reticulum, nuclear envelope, Golgi cisterns and mitochondria. In intermediate fibers these cell organelles are broken down and the liberated calcium is ionically bound to the phospholipids at the extracellular side of the fiber-limiting membrane. It is argued that calcium is prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 8 publications
(11 reference statements)
4
14
0
Order By: Relevance
“…Using electron tomographic reconstructions, we consistently found that the perimembranous precipitates along the fibres as described by Vrensen et al (1995Vrensen et al ( , 1996 were restricted to the intercellular space between the fibres since these precipitates were consistently observed to be smooth at the fibre cell membrane side irrespective of the orientation of the cross section through the reconstructed volume. The precipitates always protruded into the intercellular space, and in most cases the centre of the intercellular space was free of precipitate.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Using electron tomographic reconstructions, we consistently found that the perimembranous precipitates along the fibres as described by Vrensen et al (1995Vrensen et al ( , 1996 were restricted to the intercellular space between the fibres since these precipitates were consistently observed to be smooth at the fibre cell membrane side irrespective of the orientation of the cross section through the reconstructed volume. The precipitates always protruded into the intercellular space, and in most cases the centre of the intercellular space was free of precipitate.…”
Section: Discussionsupporting
confidence: 76%
“…No reliable data on the intercellular concentration of calcium are available. Vrensen et al (1995Vrensen et al ( , 1996 used the oxalate-pyroantimonate (OPA) technique for EM localization of free or ionically bound calcium (VanReempts, Borgers and Offner, 1982) in normal rat and human lenses. It was observed in rat and human lenses that in the epithelium and superficial cortex calcium precipitates are scanty and if present at all they are restricted to mitochondria, to the cisterns of the endoplasmic reticulum and Golgi zone and to the nuclear envelope.…”
Section: Introductionmentioning
confidence: 99%
“…Preceding organelle degradation, an increase in cytoplasmic calcium precipitates has been observed, before the Ca 2+ relocalises to the plasma membranes in organelle-free fibre cells [85,86]. It has been pointed out that the calcium measured in ultrastructural analyses of the lens only represents ionically bound Ca 2+ , since free Ca 2+ is lost during sample preparation [85], suggesting that the amount of Ca 2+ liberated during organelle breakdown is larger than that measured in this study. These data indicate that calcium signalling might be involved in the process of organelle loss in the lens.…”
Section: Intracellular Calciummentioning
confidence: 64%
“…As in most other cells, Ca 2+ in lens epithelial cells and early differentiating fibre cells has been shown to be sequestered in mitochondria, the Golgi apparatus, the endoplasmic reticulum and the nuclear envelope [85]. During fibre cell differentiation however, these organelles are broken down and Ca 2+ is liberated.…”
Section: Intracellular Calciummentioning
confidence: 91%
“…Thus there must exist calcium regulation systems in the lens, and it is of interest to identify what they are and how they change in health and in disease. Vrensen et al (3) have done an ultrastructural analysis of calcium distribution in the rat lens and have found calcium precipitates in the intermediate cortex fiber membranes, cytoplasm, and the nuclear envelope and very low levels of calcium in gap junctions, epithelial cells, and superficial fibers (3)(4)(5). The question of what the calcium-binding and -storing agents are in the lens is open; phospholipids and crystallins have been thought of as candidates.…”
mentioning
confidence: 99%